The role of attitudes and behaviours in explaining socio-economic differences in attainment at age 16 - Haroon Chowdry; Claire Crawford; Alissa Goodman (Institute for Fiscal Studies (IFS), 2010)
It is well known that children growing up in poor families leave school with considerably lower qualifications than children from better off backgrounds. Using a simple decomposition analysis, we show that around two thirds of the socio-economic gap in attainment at age 16 can be accounted for by long-run family background characteristics and prior ability, suggesting that circumstances and investments made considerably earlier in the child's life explain the majority of the gap in test scores between young people from rich and poor families. However, we also find that differences in the attitudes and behaviours of young people and their parents during the teenage years play a key role in explaining the rich-poor gap in GCSE attainment: together, they explain a further quarter of the gap at age 16, and the majority of the small increase in this gap between ages 11 and 16. On this basis, our results suggest that while the most effective policies in terms of raising the attainment of young people from poor families are likely to be those enacted before children reach secondary school, policies that aim to reduce differences in attitudes and behaviours between the poorest children and those from better-off backgrounds during the teenage years may also make a significant contribution towards lowering the gap in achievement between young people from the richest and poorest families at age 16.
Keywords: I20; I32; 330; socio-economic status; inequality; educational attainment; attitudes and behaviours; Schüler; Bildungsverhalten; Soziale Gruppe; Familie; Einkommen